Deciphering public spaces in urban contexts: geophysical survey, multi-element soil analysis, and artifact distributions at the 15th–16th-century AD Swahili settlement of Songo Mnara, Tanzania. (March 2015) - Fleisher, Jeffrey; Sulas, Federica
Abstract: Open spaces are an integral part of past urban settlement worldwide. Often large and devoid of visible traces of past activities, these spaces challenge mainstream archaeological approaches to develop methodologies suitable to investigate their history. This study uses geophysical survey, geochemical sampling and artifact distributions to examine open spaces at the Swahili stonetown of Songo Mnara, Tanzania. Initial, magnetic susceptibility survey revealed a set of anomalies associated with activities across the open spaces at the site; a systematic soil/sediment sampling program was applied to map artifact and geochemical distributions across these areas. These data provided a means to distinguish a 'public space' at the site: correlations were found between anomalies, daub, certain chemical elements (Fe, P, K, Mn) while areas without anomalies—the 'public space'—correlated with more fragmented ceramics and other chemical elements (Ca, Na, Mg, Sr). The integrated methodological framework developed at Songo Mnara offers a new way to define areas that may have functioned as 'public spaces' as well as possible activities that were carried out in them. The results suggest that open spaces at this Swahili site contained defined and protected public areas where small-scale production may have occurred. Highlights: Investigation of urban open space on the eastern African Swahili coast. Multiple techniques used: geophysical survey, artifact distributions, geoarchaeology, and test pits. Combined methodology allowed for definition of 'public space'. Public space was a protected activity area with small-scale production at margins. To decipher public space must address discrepancies/correlations between datasets.